ISSN : 1978-628X KINETIKA TRANSPOR FENOL DENGAN ADITIF SURFAKTAN DALAM TEKNIK MEMBRAN CAIR FASA RUAH - Refinel, -; Mustafa, Djufri Mustafa; Safitri, Welly; Yesti, Yulia; Anggi, Rudhy (Universitas Andalas, 2012)
Study of transport of phenol using the surfactant SDS (Sodium Dodecyl Sulfate), Tween-80 as additive in the source phase and oleic acid, Span-60 additive in the membrane phase with bulk liquid membrane techniques has been performed. Transportation system was in one way using solution of phenol 2.13 x 10 -4 M as the source phase, 30 mL of chloroform as membrane phase, a solution of 12 mL of 0.1 M NaOH as the receiving phase and stirring speed of 340 rpm. The concentration of phenol that transported into receiving phase and remaining in the source is determined by measuring phenol method using 4-aminoantipirin and monitored with a spectrophotometer. The result showed the percentage of transport of phenol into the receiving phase is 93.07% within 120 minutes without any additive surfactant, while for additive oleic acid and Span-60 the percentage of transport phenol is 97.28% and 88.84% within 90 minutes. Phenol transport system analyzed by means of a kinetic model involving consecutive irreversible first order reaction with the constants extraction of phenol from the source to the membrane (k1) of 0.0346 minute-1, 0.0304 min-1, and from the membrane phase into the receiving phase (k2) of 0.0264 min-1, 0.0309 min-1 each for additive oleic acid and Span-60 in the membrane phase. Surfactant SDS and Tween-80 additive in the source phase is not effective to decreased the transport time of the phenol in the phase bulk liquid membrane technique.